The Process of Research Writing - Krause, Steven D. (Open textbook library., 2007)
The title of this book is The Process of Research Writing, and in the nutshell, that is what the book is about. A lot of times, instructors and students tend to separate “thinking,” “researching,” and “writing” into different categories that aren't necessarily very well connected. First you think, then you research, and then you write.The reality is though that the possibilities and process of research writing are more complicated and much richer than that. We think about what it is we want to research and write about, but at the same time, we learn what to think based on our research and our writing. The goal of this book is to guide you through this process of research writing by emphasizing a series of exercises that touch on different and related parts of the research process.